Short therapy in a septic arthritis of the neonatal hip - Gatto, Antonio (Pediatr Rep, 2019)
Septic arthritis (SA) is a serious joint infection associated with significant morbidity that can cause permanent damage with articular cartilage destruction, osteonecrosis and lifelong deformities if not diagnosed and treated promptly. In neonates, because of the paucity of signs and symptoms, SA is difficult to diagnose. The treatment for SA in children is empirical antibiotic for weeks, initially intravenously, and surgical (arthrotomy) in particular for the hip and shoulder because of the high risk of sequelae in these joints. Actually, there isn’t a consensus about the duration of antibiotic treatment, because of the lack of powered studies, and a variable period from 2 weeks to 4 months has been suggested in the literature. Data in the neonatal population are very limited. We describe a case of neonatal hip arthritis with a good outcome treated with a short antibiotic course of 2 weeks.